Effect of oxytocin and some herbal preparations on induction of uterine contraction and expulsion of foetal membranes in buffaloes - GAUTAM, R P; TIWARl, R P; HORE, S K (The Indian Journal of Animal Reproduction, 2023)
Experiments were designed to study the efficacy of oxytocin and some herbal preparations in inducing uterine musclecontraction in vitro (experiment I), expulsion of fetal membranes for prevention of retention of fetal membranes (experiment II)and treatment of buffaloes with RFM (experiment 111). The result revealed dose dependent uterine contraction of estrus goat uteri,and reduction in the time required for expulsion of fetal membranes in buffaloes treated with uterotone, exapar, replanta and involonthan the control. The difference for expulsion of fetal membranes between control and uterotone, exapar involon group wassignificant. There was no significant difference for onset of first post partum estrus in control and treatment groups. Experiment IIIrevealed no significant difference on time required for expulsion of placenta and onset of first partum estrus.
Keywords: Herbal preparation; foetal membranes; oxytocin; uterine; contraction